Chlamydia trachomatis as possible cause of peritonitis and perihepatitis in young women. Issue 6119 (22nd April 1978) - Müller-Schoop, J W; Wang, S P; Munzinger, J; Schläpfer, H U; Knoblauch, M; Tammann, R W
Abstract : Of 11 young women with acute peritonitis proved by laparoscopy, seven of whom also had perihepatitis, nine had serological evidence of recent infection with Chlamydia trachomatis; In five of these nine patients high antibody titres to chlamydiae were found without laboratory evidence of gonococcal infection, while the other four had evidence of simultaneous gonococcal infection. C trachomatis may play an important part in peritoneal inflammation previously attributed only to gonococci.